Pengembangan Media E-Learning Berbasis Moodle Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas XI IPA SMA Negeri 1 Mardingding - Yolinda Christin; Pargaulan Siagian (Journal on Education, 2024)
This study aims to provide a legitimate, useful, and efficient Problem Based Learning learning paradigm for Moodle-based e-learning. This study is a development study carried out in accordance with the ADDIE development model, in which the five stages of implementation are analysis, design, development, implementation, and evaluation. 1) Based on the validity results of the format, language, content, and graphics of the learning media, Moodle-based E-Learning with Problem Based Learning (PBL) is valid, according to the study's findings. 2) The Problem Based Learning (PBL)-based Moodle-based E-Learning Media is useful and implements learning at a high standard, scoring 3.93 and receiving favorable feedback from students. 3) By meeting the four efficacy indicators in trial II, the created Moodle-based E-Learning media with Problem Based Learning (PBL) is successful in enhancing students' mathematical problem-solving abilities. These indications are: a) The classical completeness score of 88.88% satisfied the completeness requirements, meaning that 85% of pupils attained KKM, b) The average score for the completion of learning objectives was 79.99%, satisfying the requirement that at least 65% of students have completed at least 75% of each learning objective. In Trial I, it is evident that students' aptitude for solving mathematical problems grew, with a n gain value of 0.6 falling into the moderate range. Moreover, the n gain realized rose in Trial II. In trial II, the n gain value fell into the high range at 0.72.